Design of low-voltage electronically tunable current-mode multiphase sinusoidal oscillator based on single CDCTA - Chun-hua WANG; Hai-rong LIN; Yi LI; Jie JIN; Zan-ming XIA (Tongxin xuebao)
A novel current-mode multiphase sinusoidal oscillator circuit was proposed.The realized circuit using single current differencing cascaded transconductance amplifier(CDCTA)and only grounded passive elements could yield n(n being odd or even)current-output signals equally spaced in phase.It enjoyed the characteristics of simple circuit structure,low-voltage,high-output impedance,high-frequency and independently electronic adjustable of oscillation condition and oscillation frequency.CADENCE simulation and experimental results have been included to verify the theoretical analysis.